Kinetic parameters of thiamine degradation in NASA spaceflight foods determined by the endpoints method for long-term storage. (1st January 2020) - Goulette, Timothy R.; Zhou, Jiazhi; Dixon, William R.; Normand, Mark D.; Peleg, Micha; McClements, David Julian; Decker, Eric; Xiao, Hang
Highlights: Degradation kinetics of thiamine were ascertained using three data points. Kinetic parameters allowed high-accuracy predictions of thiamine loss. aw, pH, and moisture content are not primary predictors of thiamine stability. Abstract: Retention of labile vitamins such as thiamine (vitamin B1) in NASA spaceflight foods intended for extended-duration missions is critical for the health of the crew. In this study, the degradation kinetics of thiamine in three NASA spaceflight foods (brown rice, split pea soup, BBQ beef brisket) during storage was determined for the first time, using an interactive isothermal model developed by our group. Results showed that brown rice and split pea soup demonstrated resistance to thiamine degradation, while thiamine in beef brisket was less stable. Model-predicted thiamine retention in brown rice stored at 20 °C for 720 days was 55% of the original thiamine content after thermal processing, 42% for split pea soup, and 3% for beef brisket. Water activity, moisture content, and pH differences did not sufficiently explain the variation in the degradation kinetics of thiamine among these foods.